2013
DOI: 10.1002/jcb.24512
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐dependent effects of nicotine on proliferation and differentiation of human bone marrow stromal cells and the antagonistic action of vitamin C

Abstract: A range of biological and molecular effects caused by nicotine are considered to effect bone metabolism. Vitamin C functions as a biological antioxidant. This study was to evaluate the in vitro effects of nicotine on human bone marrow stromal cells and whether Vitamin C supplementation show the antagonism action to high concentration nicotine. We used CCK-8, alkaline phosphatase (ALP) activity assay, Von Kossa staining, real-time polymerase chain reaction and Western Blot to evaluate the proliferation and oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 41 publications
1
19
0
1
Order By: Relevance
“…It has also been reported that oxidative stress may result in changes in the expression of cell cycle‐related proteins, including cyclin D1, p21, and p27 . Another study also suggested that the decrease in proliferation depends on the production of ROS . Based on the results of this previous study and our study, we suggest that the inhibition of cell proliferation by CSE observed in the present study might have been because of oxidative stress.…”
Section: Discussionsupporting
confidence: 81%
“…It has also been reported that oxidative stress may result in changes in the expression of cell cycle‐related proteins, including cyclin D1, p21, and p27 . Another study also suggested that the decrease in proliferation depends on the production of ROS . Based on the results of this previous study and our study, we suggest that the inhibition of cell proliferation by CSE observed in the present study might have been because of oxidative stress.…”
Section: Discussionsupporting
confidence: 81%
“…Whereas reduced bone mineral density has been reported in smokers, a careful search of the literature reveals that actual knowledge of the bone ultrastructure in smokers is missing. Another interpretation, supported by in vitro studies, is that smoking affects bone in a graded manner, necessitating both distinct anamnestic details and the implementation of an objective marker of smoking, such as the concentration of nicotine. Furthermore, as suggested by the present study, the maxilla and mandible respond differently to the constituents of tobacco smoke.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that nicotine down-regulates the expression of osteogenic genes [14]. The three main genes involved in bone metabolism include alkaline phosphatase (ALP), osteocalcin (OC) and bone sialoprotein (BSP) [3,15]. Alkaline phosphatase plays an important role in mineralization of collagenous bone matrix and is related to the activity of osteoblasts [16].…”
Section: Introductionmentioning
confidence: 99%
“…Alkaline phosphatase plays an important role in mineralization of collagenous bone matrix and is related to the activity of osteoblasts [16]. Osteocalcin [3] and BSP [17] are the main non-collagenous proteins in bone, which are involved in regulation of the mineralization process. Expression of OC occurs at a late stage of osteogenic differentiation and is a characteristic marker of mature cells of osteoblastic lineage [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation